A study on the model for the minimum wages act in Malaysia and its implication towards Malaysia’s labour law / Mohamed Azhar Shah Zainal Arif, Nur Ain Mohamad Salleh and Wan Arissa W. Rosli. - Zainal Arif, Mohamed Azhar Shah; Mohamad Salleh, Nur Ain; W. Rosli, Wan Arissa (Faculty of Law, 2011)
The issue of implementation of minimum wage for the worker in Malaysia has been debated for quite some time. Few campaigns have been organized to call for the government to consider this matter relating to the rights of the workers in the country. Everyone should be given the opportunity to live a balance lifestyle and free from exploitation and this can be achieved by imposing a suitable minimum wage for the workers regardless of any form of discrimination. This paper is aimed to find a suitable model or system of implementation of minimum wage to be adopted in Malaysia by comparing it to the system in few other countries like United Kingdom, Australia and also India. This research is focusing on the adequacy of Wages Council Act 1947 and Employment Act and comparison of these Acts with another country. This project touched about laws and its components. The qualitative type of research, semi-structured interviews and library-based internet research had been used as a method in conducting this research in determining the weaknesses and practicability of the laws. The importance of literature review is to get a better understanding of the topic to achieve the objectives of this study. In addition, it helps to get more information such as from paper cutting or articles. The proposed outcome from this research is we expect to find out solutions to handle this issue from getting worst in our country.